Arbutus unedo L. and its benefits on human health - Oliveira, Ivo (2014)
Arbutus unedo has been long used in folk medicine, throughout Mediterranean countries, with the employment of infusions and decoctions of almost all parts of this plant: leaves, fruits, barks and roots. The application of these traditional remedies arises from several health-promoting characteristics, for treatment of gastrointestinal and urological problems, hypertension and cardiac diseases, diabetes and as anti-inflammatory agent, among other interesting properties. Antioxidant ability of A. unedo shrub is also known, and antimicrobial activity has also been reported. Several compounds present in different parts of the plant may be linked to these properties. Included in those are carotenoids, flavonoids, phenolic acids and vitamins (C and E). Other bioactive compounds may be also found in different parts of A. unedo, like terpenoids and organic acids. This review will focus on the known composition of several parts of A. unedo, their antioxidant ability and traditional use, and the available data sustaining the rationality of the use as part of folk medicine.